Misje i cele instytucji kultury - Joanna Ablewicz (Studia Prawa Publicznego)
This article uses various examples to show how the different goals of cultural institutions are being realised in practice. The mission of each cultural institution is the starting point for many plethora of tasks carried out by the in- stitution. It is clearly intended to exhibit why and for whom the institution exists, what it does, what its values are and what it aims to become. This mission should be unique for each cultural institution and permanent. Selected mission state- ments are discussed with examples to demonstrate whether cultural institutions articulate it correctly and understand their importance. An objective, on the other hand, is one of the elements of a cultural institution’s mission; it is something that the cultural institution wants to achieve through the actions it undertakes and, as indicated, follows from the mission. Objectives are a detailed refinement of the mission and may change in response to the changing environment in which the cultural institution operates. The article discusses the objectives of cultural institutions deriving from specific legal acts, and the way in which they are formulated by individual entities, and also analyses  statutes, regulations and other acts concerning how specific cultural institutions function. Particular attention is paid to the objectives of cultural institutions from the perspective    of the recipient, as it is the recipient who really decides (through participation  in the cultural activities of the institution) whether the institution properly ful- fils its objectives. An analysis of selected goals of cultural institutions shows that, as a rule, these institutions define their objectives in a very general way, merely repeating the wording indicated, for example, in the Cultural Activities Act. Objectives formulated in this way do not correctly reflect the scope of the cultural institution’s activities.